Get well soon, Adam - Sarah, Duchess of York, 1959-; Cunliffe, Ian (New York : Sterling Children's Books, 2011)
Just as Adam is wondering if he will ever be healthy again, he is cheered by a visit from one of his best friends who brings cards from his classmates. Includes ten hints for parents to help children cope with being sick.
School Library Journal
School Library Journal, August 2011
1.5
K-3
K-3
Keywords: Ilness -- Fiction; Ilness -- Fiction; Ilness -- Fiction; Picture books for children